Checklist of fishes at Pergau Lake, Jeli, Kelantan, Malaysia - Mohd Alias, Malisa Ilyana; Kambali @ Hambali, Kamarul Ariffin; Mohamad Amir Hamzah, Aainaa Syazwani; Mohd Fauzi, Norashikin; Hassin, Nor Hizami; Sow, Ai Yin (Penerbit Universiti Sains Malaysia, 2019)
A survey was conducted to determine the diversity of fish in Pergau Lake, Jeli, Kelantan, Malaysia from 2 September to 18 October of 2016. Fish samples were collected at seven random sampling stations around the lake by using setting trap method. The collected samples were preserved in 10% formalin solution and delivered to the laboratory for further identification process. Fourteen species, namely as Hemibagrus nemurus, Hampala macrolepidota, Clarias batrachus, Channa striata, Cyprinus carpio, Poropuntius smedleyi, Pangasius sp., Oreochromis niloticus, Oreochromis mossambicus, Leptobarbus hoevenii, Neolissochilus hexagonolepis, Tor tambroides, Osteochilus hasselti and Neolissochilus soroides, comprising of six families were collected during this study. From this study, family of Cyprinidae was the dominant species in Pergau Lake with exactly 50% of catch percentage, followed by family of Bagridae (29%), Cichlidae (10%), Clariidae (5%), Channidae (3%) and Pangasiidae (3%). This study shows that there is still a diversity of fish species in Pergau Lake, showing that the water and its environmental condition is very good.